2022
DOI: 10.2478/ahr-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Revitalization and landscape design of the park in Stari Mikanovci, Croatia; role of existing vegetation in generating new landscape solutions

Abstract: In this paper, the procedures and indicators of systematic inventorisation and analysis of the existing vegetation of urban landscapes are presented and applied. The analysis of the vitality of existing trees was performed using the Visual Tree Assessment (VTA) method on the location of Park in Stari Mikanovci, Croatia. The results of these analyses were used as a basis for the protection and care of existing vegetation, but also their implementation in the design. For this purpose, four different conceptual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…An analysis conducted on tree species identification in an urban setting, evaluating the added value of fusing spectral imagery with Light Detection and Ranging (LiDAR) data. They concluded that the fusion of these two data sources significantly improves tree species mapping results [12]. On the other hand, a review conducted on tree species classification without specifically focusing on urban areas.…”
Section: International Journal Of Innovative Research In Computer Sci...mentioning
confidence: 99%
“…An analysis conducted on tree species identification in an urban setting, evaluating the added value of fusing spectral imagery with Light Detection and Ranging (LiDAR) data. They concluded that the fusion of these two data sources significantly improves tree species mapping results [12]. On the other hand, a review conducted on tree species classification without specifically focusing on urban areas.…”
Section: International Journal Of Innovative Research In Computer Sci...mentioning
confidence: 99%